Validation of a non-conservative mechanical model applied to the low energy impact phenomenon (2018)
The impact of materials is undoubtedly the object of research, due to the dynamic condition inherent in the bodies that interact in our universe. This work places special emphasis on the method of plate bending, which, due to its geometric configuration, interprets real impact situations to which some bodies are subjected, in addition to the low energy technique in which the energy available in the impactor is less than that absorbed in the breaking process, makes it possible to obtain information on the material in the elastic, plastic, initiation and crack propagation range. For research, the contribution of technological progress in instrumented test equipment by electronics is important, as it allows us to record much more information on the evolution of the contact between the impactor and the sample step by step. This information must be further processed and this phase of the research requires programming, modelling and simulation of the test dynamics to interpret or even predict the different phenomena that converge in the fraction of time in which the impact occurs. In this sense, our objective has been to study the physical behavior of different thermoplastic materials and their response to impact requests and to develop a series of models that try to simulate the phenomenon, in order to help us establish what happens at each stage of it, this is achieved using powerful mathematical tools, new contributions from the scientific community and continuous experimentation achieved in the laboratory. So that more knowledge can be obtained in this field.